Strategic leadership and It's Impact on Achieving The Organizational Reputation - سعيد, هديل كاظم; عباس, زياد علي (Journal of Economics and Administrative Sciences, 2017)
Abstract :This research aims to examine the correlation and the impact of Strategic leadership on Achieving Organizational in some of establishments in ministry of construction and housing which is under public founds, Starting from the importance of research in public organizations and the importance of these organizations to the community, it is rely descriptive analytical methods in achievement of this research, the research involved board of directors, Data has collected from (92) respondents, represent the respondent society exclusively and comprehensively, it involved the general directors, assistant general directors and heads of department, The research relied programs (Excel 2010, Spss V.21), moreover, some of descriptive statistics methods to test research's Hypotheses, The researcher is attain to the existence of relationship and impact of strategic leadership in organizational reputation, the research included four axes first went to the methodology  and second to theoretical frame and the third to view and analyze the results and test hypotheses while the fourth was devoted to the conclusions and recommendations .